General Characterization of Cuticular Membrane Isolated from Agave salmiana - Perez-Espana, V. H.; Cuervo-Parra, J. A.; Paz-Camacho, C.; Morales-Ovando, M. A.; Gomez-Aldapa, C. A.; Rodriguez-Jimenes, G. C.; Robles-Olvera, V. J.; Lopez-Perez, P. A.; Romero-Cortes, T. (International Journal of Bio-resource and Stress Management, 2019)
The plants of the genus Agave have a characteristic cuticular membrane that serves as an adaptation to arid conditions. The cuticular membrane of Agave salmiana is commonly used for the elaboration of certain regional culinary dishes in Mexico, due in part to its particular flavor. Unfortunately, when the cuticle is removed from the plant, it dehydrates very quickly and becomes brittle, which makes it necessary to extract more cuticles. In this work, our aim was to expand the knowledge on the composition of the A. salmiana cuticular membrane. Within the results it was found that the moisture content of the cuticular membrane of A. salmiana ranges between 50 and 60%. Concerning Water activity (aw), there were no significant differences between diverse storage temperatures (2, 8 and 22 °C). On the other hand, considering the hue angle and luminosity, the obtained values ​​were 80.25±1.29 and 70.85±0.65, respectively. Although, no significant changes were observed. The thickness of the cuticle of A. salmiana was 129±1.9 μm and the fibers had a thickness of 30.7±3 μm. The heat flow thermograms correspond to those reported for the fatty acid transition (50 to 100 °C). This work contributes to the overall characterization of the A. salmiana cuticular membrane including the morphology, distribution and size of stomatal complexes and epidermal cells.